Is it time to reconsider prophylactic antimicrobial use for hematopoietic stem cell transplantation? a narrative review of antimicrobials in stem cell transplantation. Issue 10 (3rd October 2021) - Jahan, Dilshad; Peile, Ed; Sheikh, Md Arif; Islam, Salequl; Parasnath, Sharlene; Sharma, Paras; Iskandar, Katia; Dhingra, Sameer; Charan, Jaykaran; Hardcastle, Timothy Craig; Samad, Nandeeta; Chowdhury, Tajkera Sultana; et al.
ABSTRACT: Introduction: Hematopoietic Stem Cell Transplantation (HSCT) is a life-saving procedure for multiple types of hematological cancer, autoimmune diseases, and genetic-linked metabolic diseases in humans. Recipients of HSCT transplant are at high risk of microbial infections that significantly correlate with the presence of graft-versus-host disease (GVHD) and the degree of immunosuppression. Infection in HSCT patients is a leading cause of life-threatening complications and mortality. Areas Covered: This review covers issues pertinent to infection in the HSCT patient, including bacterial and viral infection; strategies to reduce GVHD; infection patterns; resistance and treatment options; adverse drug reactions to antimicrobials, problems of antimicrobial resistance; perturbation of the microbiome; the role of prebiotics, probiotics, and antimicrobial peptides. We highlight potential strategies to minimize the use of antimicrobials. Expert Opinion: Measures to control infection and its transmission remain significant HSCT management policy and planning issues. Transplant centers need to consider carefully prophylactic use of antimicrobials for neutropenic patients. The judicious use of appropriate antimicrobials remains a crucial part of the treatment protocol. However, antimicrobials' adverse effects cause microbiome diversity and dysbiosis and have been shown to increase morbidity and mortality.